Eklektisisme Hukum Perikatan Nasional (Potensi, Kelemahan, Peluang, dan Ancaman Implikasinya bagi Dinamika Ekonomi Syariah di Indonesia) - Nurul Mahmudah; Muhammad Yusuf Putra (Nizham Jurnal Studi Keislaman, 2020)
This paper discusses the existence of a sharia system in banking that collaborates with the conventional banking system that has long been implemented in Indonesia. In this collaboration, it is believed that it will create positive and negative effects on the regulatory side or its rationalization for the dynamics of Islamic Economics in Indonesia. This paper uses library research with a qualitative approach with a descriptive nature that tends to use analysis. In this approach, the subject's perspective is emphasized, namely the process and meaning of the research carried out. The results of this paper are that the legal eclecticism of national engagement here has potential advantages, weaknesses, opportunities and threats for the sharia system and conventional systems in banking itself. In the positive side, there are regulations and ease of access to favorable bank itself, while the negative can be seen from the decline in public confidence in the system of sharia in banking due to the mixing of the system both the system then the conventional banking and sharia considered only different in name only.